Mo(vi)mentos autobiográficos: historiando fragmentos narrativos de experiências de vida docente e discente em artes visuais - Ferreira, Luiz Carlos Pinheiro (2015)
This doctoral research, with emphasis on autobiographical narrative, presents issues focusing on mo(ve)ments seen from the rearview mirror of life. This retro(re)located archaeological view situates images, memories and fragments of my life history, leading me to a (re)visitation of school time, processes of teacher training and teaching practice in the field of Visual Arts. The study articulates and includes analysis related to the processes of life narrative and teacher training of student’s collaborators earning the Teacher Education Degree in Visual Arts at the University of Brasilia. The research analyses pedagogical episodes lived in the classroom, reflecting on the temporality of biographical experience and existence to think the place of narrative in the context of connections between the know-how as a possibility for transformation and self-transformation of the subjects involved. The narrative fragments of the history of life give the research epistemological coherence consolidating interest in autobiographical approach as research perspective and as a practical training, enabling a (re)construction of archaeological subject. Self-reflexive references and biographical reflexivity are used as theoretical allowance to (re)position historical consciousness about learning and lived experiences throughout life. This route took me to design a methodological tripod based in teaching episodes, in interviews and focal groups as orientation to analyze the data produced in the field of research which showed the self narrative as a way that projects a subject involved in passages, territory of sensibilities configured through marks, affections and traces resulting from lived experiences, that is, a subject under training who learns not only through pedagogical practice but also giving place to whatever comes, and yet, learning to be a place, a port and a space for happenings and mo(ve)ments of life as a necessary way to knowledge and self narrative.